Reactive oxygen species signaling and stomatal movement in plant responses to drought stress and pathogen attack - Qi, Junsheng; Song, Chun‐Peng; Wang, Baoshan; Zhou, Jianmin; Kangasjärvi, Jaakko; Zhu, Jian‐Kang; Gong, Zhizhong (Journal of integrative plant biology, 2018)
Stomata, the pores formed by a pair of guard cells, are the main gateways for water transpiration and photosynthetic CO2 exchange, as well as pathogen invasion in land plants. Guard cell movement is regulated by a combination of environmental factors, including water status, light, CO2 levels and pathogen attack, as well as endogenous signals, such as abscisic acid and apoplastic reactive oxygen species (ROS). Under abiotic and biotic stress conditions, extracellular ROS are mainly produced by plasma membrane‐localized NADPH oxidases, whereas intracellular ROS are produced in multiple organelles. These ROS form a sophisticated cellular signaling network, with the accumulation of apoplastic ROS an early hallmark of stomatal movement. Here, we review recent progress in understanding the molecular mechanisms of the ROS signaling network, primarily during drought stress and pathogen attack. We summarize the roles of apoplastic ROS in regulating stomatal movement, ABA and CO2 signaling, and immunity responses. Finally, we discuss ROS accumulation and communication between organelles and cells. This information provides a conceptual framework for understanding how ROS signaling is integrated with various signaling pathways during plant responses to abiotic and biotic stress stimuli. Stomata are the main gateways for water transpiration and photosynthetic CO2 exchange, as well as pathogen invasion in land plants. Stomatal movement is regulated by a combination of environmental factors including water status, light, CO2 levels and pathogen attack, as well as abscisic acid and apoplastic reactive oxygen species (ROS).